The presumption of the harm caused by anticompetitive conducts, jurisprudence of the German Federal Court (Bundesgerichtshof) - Suderow , Julia; Krüger, Carsten (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
According to the German Supreme Court or BGH, it can be presumed that the anticompetitive exchange of information leads to a price increase and thus to a harmful effect. In this article we present the development of jurisprudence of the German Supreme Court through the rulings on the beer cartel, the truck cartel and the cosmetics cartel. The findings concerning German administrative law are analysed as well as those concerning civil tort law.
Keywords: Presumption of the harm; Bundesgerichtshof; German Federal Court; exchange of information; trucks; beer; Schlecker; Bundeskartellam; Competition law; follow on